The Study of Making Biomass Briquettes from Spent Coffee Ground - Ramadhani Fithratullah (Journal of Environmental Engineering and Waste Management, 2022)
Abstract: Nowadays coffee becomes a culture in the community. The growing demand is triggered by the younger generation and newfound locally produced coffee. That can be seen in the rapid growth of modern coffee shop like “kopi Kenangan” that reach 700 outlets in one year led to consumption means rapid waste. Objectives: The objective of this research is to know whether the Density, ash content and volatile of spent ground coffee briquets comply or not to the briquets Indonesia standard in Forestry Research and Development Agency 1994. Method and results: In this research spent coffee ground is used by fixed volume with the difference in coffee to tapioca to water ratio to find perfect balances. waste from local coffee shop taken to be treated into bio briquets then density, water content, and ash content is compared to briquets Indonesia standard in Forestry Research and Development Agency 1994 There are three treatments with variations on the amount of coffee where the volume of the briquets is kept the same. The volume is kept the same because the result is nearly mimicking one of the briquets design in Minister of Energy and Natural Resources Regulation No. 47 of 2006 the briquets from the spent coffee ground itself have passed the standard of density, ash content, and volatile matters Sample A has the best performance than others. Conclusion: Based on the results of the research using espresso spent coffee, it is very possible if it is processed in the right way, the most promising performance is in the composition of sample B but it does need to be improved. Based on practice of research and the result itself researcher suggest that the raw material preparation is done in longer period around 5 hours until 24 hours at 210 oC, then carbonation process is done at 350oC until 400 oC to gain better result.